Fossils in a Digital Age: Preserving 3D Fossil Data in Digital Libraries - Eber, Anneliese (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2023)
Digital libraries are a powerful tool for preserving and disseminating information in a technology-driven world. Providing options for housing non-traditional information, such as three-dimensional (3D) data, digital libraries also address barriers (e.g., geographic location and physical space) that affect traditional libraries. While there are certainly still barriers that may prevent users from accessing and utilizing digital content, digital libraries offer ways of preserving, housing, and disseminating non-traditional information that physical libraries cannot. Within the anthropological community, digital libraries can serve as a method of housing 3D fossil data. There are unique challenges and barriers associated with studying fossils that digital libraries help to break down. Through the preservation and dissemination of 3D fossil data, researchers across the globe can work with fossil data without the concerns associated with handling fragile fossils. However, such 3D digital libraries are not without challenges. While there are clear standards and metadata schemas (e.g., RDA and DCMI) for digital libraries containing traditional materials, no such standardization exists for digital libraries containing 3D data. As such, metadata requirements and elements for existing 3D digital libraries are inconsistent and may lack important details about the data, which can compromise functionality. This paper explores trends and challenges that digital libraries containing 3D data experience and highlights best-practice solutions for future 3D digital libraries to overcome these challenges.